2014
DOI: 10.1007/s00404-014-3598-5
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 plays a critical role in epithelial ovarian cancer

Abstract: We could hypothesize that Annexin A2 acted a critical role in EOC cell proliferation, and may be used as a potential and novel therapeutic target for EOC. These data suggest that Annexin A2 may promote the progression of EOC and be a therapeutic target for EOC therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 24 publications
1
22
0
3
Order By: Relevance
“…In the present data, AnxA2 showed high abundance on 2‐DE map of OC relative to control tissue samples. In that, AnxA2 has previously been found associated with OC in the literature, where some researchers reported its upregulation while others described its downregulation, relative expression of AnxA2 further validated by WB. In concordance with 2‐DE data, WB analysis confirmed upregulation of AnxA2 in OC comparative to the control tissues (Figure 3A,B).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In the present data, AnxA2 showed high abundance on 2‐DE map of OC relative to control tissue samples. In that, AnxA2 has previously been found associated with OC in the literature, where some researchers reported its upregulation while others described its downregulation, relative expression of AnxA2 further validated by WB. In concordance with 2‐DE data, WB analysis confirmed upregulation of AnxA2 in OC comparative to the control tissues (Figure 3A,B).…”
Section: Resultsmentioning
confidence: 84%
“…However, AnxA2 regulation in OC was found disputed, some researchers reporting its high abundance while another study reported low abundance in OC. Our study showed upregulation of AnxA2 in 80% OC cases by WB.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of heterozygosity (LOH) and gene sequencing analysis investigate the possibility of CNTN4 to function as tumor suppressor gene in ovarian cancer [56]. ANXA2 is a calcium-binding cytoskeletal protein aberrantly expressed in a wide spectrum of cancers and in EOC may promote cell proliferation [57]. …”
Section: Resultsmentioning
confidence: 99%
“…70E-02 tissue [55] Q9JJ19 Na (+)/H (+) exchange regulatory cofactor (NHRF1) [56] P24594 Insulin-like growth factor-binding protein 5 (IBP5)…”
Section: Urine Proteome Changes In Nutu-19 Cell Intraperitoneal-injecmentioning
confidence: 99%
“…is overexpressed in carcinoma tissues compared with normal tissue and has a critical role in EOC cell proliferation; it has the potential to be used as a novel therapeutic target for EOC [56] . Insulin-like growth factor-binding protein 5 (IBP5) is overexpressed in high-grade serous carcinomas compared to normal surface epithelium and might play a role in the development of this disease [66] .…”
Section: Urine Proteome Changes In Nutu-19 Cell Intraperitoneal-injecmentioning
confidence: 99%